Child and parental sleep in young children with epilepsy: A population‐based case‐control study. Issue 3 (8th July 2018) - Reilly, Colin; Atkinson, Patricia; Memon, Ayesha; Jones, Chloe; Dabydeen, Lyvia; Cross, J. Helen; Das, Krishna B.; Gillberg, Christopher; Neville, Brian G.R.; Scott, Rod C.
Summary: Objective: To determine the prevalence of parent‐reported sleep problems in young children with epilepsy and their parents, and to compare findings with those in a non–epilepsy‐related neurodisability (neurodevelopmental/neurological difficulties) group. Method: Parents of young children (1–7 years) with epilepsy (n = 48 [91% ascertainment]) completed the Child Sleep Habits Questionnaire (CSHQ). Parents (mothers and fathers) also completed the Pittsburgh Sleep Quality Index (PSQI) and the Iowa Fatigue Scale (IFS) in relation to their own functioning. The responses of parents of children with epilepsy were compared with parents of developmental‐, age‐, and gender‐matched children with nonepilepsy‐related neurodisability (n = 48). Results: There was not a significant difference in the proportion of children with epilepsy and the children with neurodisability scoring in the at‐risk range on the CSHQ (81% vs. 71% respectively) (p = 0.232). 62% of mothers and 44% of fathers of children with epilepsy had 'poor quality sleep' on the PSQI; there was not a significant difference between mothers of children with epilepsy and those of children with neurodisability (p = 0.526) or IFS (p = 0.245) total scores. However, mothers of children with epilepsy had significantly more difficulties on the productivity subscale of the IFS (p = 0.004). There were no significant differences between fathers' scores on either measure. In the epilepsy group, child behavioral problems (p = 0.001) were independently associated with child sleep difficulties and maternal mental health problems were associated with parental sleep difficulties (p = 0.04) and fatigue (p = 0.018). Significance: Young children with epilepsy and their parents have a high rate of sleep difficulties. There is a need to develop effective interventions for this population, taking into consideration of the role of child behavioral problems and parental mental health difficulties.